Screening, Diagnosis, and Management of Open Angle Glaucoma: An Evidence-Based Guideline for Canadian Optometrists - MacIver, S.; MacDonald, D.; Prokopich, C. Lisa (Canadian Journal of Optometry, 2019)
Glaucoma is the most common form of irreversible blindness in the world, and second only to cataract among all causes of blindness. There is still no universally agreed-upon definition of glaucoma, and as such, it remains a condition for which there are differing views on the classification of individuals within the continuum of suspicion through diagnosis. Regardless, there appears to be consensus that glaucoma refers to a group of diseases that manifest as a characteristic progressive optic neuropathy and retinal ganglion cell loss that eventually leads to a permanent loss of visual field. Glaucoma is a major public health issue because individuals are typically asymptomatic until end stages of the disease when the associated vision loss is significant and irreversible. Studies have shown that the prevalence of undetected glaucoma is as high as 50% even in high income areas including North America and Australia, increasing to 90% in middle and low income areas such as Asia and Africa. This is at least in part a result of inadequate screening tools and strategies to detect this asymptomatic disease: without more individuals accessing routine eye examinations, glaucoma will continue to go undetected. Vision loss from glaucoma imposes significant societal and economic burdens that increase with disease severity: the direct costs of vision loss from glaucoma exceed 300 million annually in Canada, and approach 2 billion across North America.